METHODS FOR THE OPTIMAL ORGANIZATION OF PHYSICAL EDUCATION PROCESSES FOR CHILDREN IN PRESCHOOL AND PRIMARY EDUCATION (Scientific journal of the Fergana State University, 2026)
The article analyzes the theoretical and practical aspects of effectively organizing physical education and health-improvement processes for children of preschool and primary school age in our country. It highlights the impact of physical activity on children's morphofunctional development as well as on the condition of the respiratory and cardiovascular systems. The research results confirm that regular physical exercises in preschool educational institutions significantly improve children’s motor skills, endurance, and coordination. The importance of properly organizing the motor regimen, structuring physical education sessions, and applying modern pedagogical technologies is also emphasized. The article provides practical recommendations for the scientifically grounded organization of physical education and health-improving activities and for increasing their effectiveness.